2008
DOI: 10.2337/dc07-2094
|View full text |Cite
|
Sign up to set email alerts
|

Multisystemic Therapy for Adolescents With Poorly Controlled Type 1 Diabetes

Abstract: OBJECTIVE -The study aim was to determine if multisystemic therapy (MST), an intensive home-based psychotherapy, could reduce hospital admissions for diabetic ketoacidosis (DKA) in youth with poorly controlled type 1 diabetes over 24 months. Potential cost savings from reductions in admissions were also evaluated. RESEARCH DESIGN AND METHODS-A total of 127 youth were randomly assigned to MST or control groups and also received standard medical care.RESULTS -Youth who received MST had significantly fewer hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(73 citation statements)
references
References 10 publications
1
71
0
1
Order By: Relevance
“…T1DM is an ambulatory-care sensitive condition, defined as a group of medical conditions typically managed in an ambulatory setting, whereby an admission to hospital indicates a potentially avoidable complication and is an indirect indicator of access and overall quality of outpatient care. 40,41 DKA is generally avoidable and its occurrence in children and adolescence with established T1DM may indicate poor outpatient diabetes mellitus care and could be prevented with comprehensive multidisciplinary outpatient care and improved adherence to diabetes management. Table 2 outlines the risk factors for DKA among youth with established T1DM.…”
Section: Diabetic Ketoacidosis In Established Type 1 Diabetes Mellitusmentioning
confidence: 98%
See 1 more Smart Citation
“…T1DM is an ambulatory-care sensitive condition, defined as a group of medical conditions typically managed in an ambulatory setting, whereby an admission to hospital indicates a potentially avoidable complication and is an indirect indicator of access and overall quality of outpatient care. 40,41 DKA is generally avoidable and its occurrence in children and adolescence with established T1DM may indicate poor outpatient diabetes mellitus care and could be prevented with comprehensive multidisciplinary outpatient care and improved adherence to diabetes management. Table 2 outlines the risk factors for DKA among youth with established T1DM.…”
Section: Diabetic Ketoacidosis In Established Type 1 Diabetes Mellitusmentioning
confidence: 98%
“…In a randomized controlled trial in 127 adolescents with poorly controlled T1DM, intensive home-based psychotherapy over 2 years was associated with sustained reduction in hospital admissions compared with baseline or to controls over the full period. 41 This intensive intervention was expensive ($6934 per patient), but this cost was offset by reduced admissions for DKA. A subsequent trial in 146 adolescents with T1DM or type 2 diabetes mellitus showed that this approach was superior to telephone support in improving glycemic control over 12 months.…”
Section: Preventing Diabetic Ketoacidosismentioning
confidence: 99%
“…The intervention content and format varied based on individual needs and barriers to T1D management, and drew from other empirically supported approaches such as behavioral contingencies, cognitive–behavioral therapy, and case management. MST for diabetes has demonstrated increased adherence to diabetes management tasks, fewer hospitalizations, lower health care costs, and improved glycemic control up to 24 months postintervention compared with standard care or a telephone support intervention (Ellis et al, 2012; Ellis et al, 2008). …”
Section: State Of the Science Reviewmentioning
confidence: 99%
“…In addition, families in the intervention group received a 6-month therapy that included adherence-related problem-solving training within the family, school, and health systems, as well as communication training and a social support intervention. As the primary outcome variable, significantly fewer hospital admissions occurred among adolescents of the MST intervention compared with controls [55].…”
Section: Psychological Interventions To Improve Metabolic Control Andmentioning
confidence: 98%